A Comparison of Flame Spread Characteristics over Solids in Concurrent Flow Using Two Different Pyrolysis Models. (5th April 2011) - Tseng, Ya-Ting; T'ien, James S.
Abstract : Two solid pyrolysis models are employed in a concurrent-flow flame spread model to compare the flame structure and spreading characteristics. The first is a zeroth-order surface pyrolysis, and the second is a first-order in-depth pyrolysis. Comparisons are made for samples when the spread rate reaches a steady value and the flame reaches a constant length. The computed results show (1) the mass burning rate distributions at the solid surface are qualitatively different near the flame (pyrolysis base region), (2) the first-order pyrolysis model shows that the propagating flame leaves unburnt solid fuel, and (3) the flame length and spread rate dependence on sample thickness are different for the two cases.